Host Determinants on Death of Covid-19 Patients - Amirullah, Andi Nailah; Sasmita, Salki; Nurmala, Dewi Rizki (Sean Institute, 2022)
The 2019 corona virus infection (COVID-19) pandemic is a problem that is being faced in more than 200 countries in the world. The number of deaths from COVID-19 also increased to 33,673 in the world. The number of positive cases of COVID-19 worldwide has reached 1,936,700 people. Comorbid hypertension and diabetes mellitus, male gender, and active smoking are risk factors for SARS-Cov-2 infection. The purpose of this study was to determine the host determinants (age, sex and comorbidities) in the death of Covid-19 patients in the hospital. Wahidin Sudirohusoso, Makassar City. This study uses a quantitative approach with a case control research design using secondary data sources from medical record data. Data analysis was carried out by univariate, bivariate, and multivariate analysis. The population in this study were all Covid-19 patients diagnosed and receiving treatment at RSUP Dr. Wahidin Sudirohusodo. The minimum required sample size for each case-control group is 68, with a ratio of 1:1. The results of the OR calculation showed that respondents aged 46 years had 5,958 times more deaths due to Covid-19 compared to the age group <46 years (95% CI 2,817-12,6042,817-12,604). The results of the Chi Square test show that there is no significant relationship between gender and the death of Covid-19 patients (P Value 0.195), so that respondents with male sex do not necessarily experience death from Covid-19 compared to female sex. The results of the OR calculation show that respondents who have comorbidities are 38,400 times more likely to die from Covid-19 than respondents who do not have comorbidities (95% CI 38,400 (12,319-119,694)). The variable that was significantly related to the death of Covid-19 patients was comorbidity with an OR of 3.648, meaning that Covid-19 patients with comorbidities had 3. There is a significant relationship between age and comorbidities with the death of Covid-19 patients and there is no significant relationship between gender and the death of Covid-19 patients. The results of the multivariate analysis showed that the variable that was significantly related to the death of Covid-19 patients was comorbid with an OR of 3.648. The active role of health workers is to carry out the socialization of Covid-19 prevention, so that it is hoped that the community will be able to take preventive measures and can reduce the death rate due to Covid-19.